Foresight into climate-compatible futures for cities and regions. (2018) - Ahamer, Gilbert
This article describes methods of climate-related action for sub-governmental bodies such as cities and regions. Durable ways of engagement within the Conference of the Parties (COP) negotiation dynamics are searched, analysed and proposed. The brief institutional and financial analysis covers the past decade and includes suggestions for concrete measures on municipal and regional levels. Overall, this article is intended to guide and inspire cities and regions towards concrete action to optimise their negotiation tactics, climate financing approaches, concrete project definitions and project-financing proposals.